Developmental Changes in Pain and Spinal Immune Gene Expression after Radicular Trauma in the Rat - Barr, Gordon A.; Wang, Shaoning; Weisshaar, Christine L.; Winkelstein, Beth A. (Frontiers in Neurology, 2016)
Neuropathic pain is an example of chronic pain that develops after nerve injury and is less frequent in infants and children than in adults. Likewise, in animal models of neuropathic pain, allodynia and hyperalgesia are non-existent or attenuated in the infant, with a “switch” during development by which acute nerve injury transitions to chronic pain. Concomitant with the delay in neuropathic pain, there is a parallel delay in the ability of nerve injury to activate the immune system. Models of neuropathic pain in the infant have used various ligation methods and find that neuropathic pain does not occur under after postnatal day 21-28 (PN21-PN28), linked to activation of immune processes and developmental regulation of anti-inflammatory cytokines. We applied a model of neuropathic pain in the adult using a transient compression of the cervical nerve or nerve root in infant rats (injured at 10, 14, 21 or 28 days of age) to define transition periods during which injury results in no change in thermal and mechanical pain sensitivity or in short term changes in pain. There was little to no hyperalgesia when the injury was imposed at PN10, but significant thermal hyperalgesia and mechanical allodynia one day after compression injury when performed at PN14, 21 or 28. Thermal withdrawal latencies return to near baseline by 7 days post-surgery (PS7) when the injuries were at PN14, and lasted up to 14 days when imposed at PN28. There was mechanical allodynia following nerve injury at 7 or 14 days after injury at PN14. Measurements of mRNA from spinal cord at 1, 7 and 14 days post-injury at PN14, 21, and 28 showed that both the magnitude and duration of elevated immune markers and chemokines/cytokines were greater in the older animals, corresponding to the development of hyperalgesia. Thus we confirm the late onset of neuropathic pain but found no evidence of emergent hyperalgesia if the injury was before PN21/28. This may be due to the use of a transient, and not sustained, compression compared to that of ligation models.